Their Own Step Forward: Young Philologists of the Urals (Review of Scientific Conferences and Publications) (Филологический класс, 2020)
The authors of the present analytical review attempt to demonstrate the diversity of forms, areas of work and current research trends in the field of student science in the Urals region. The scope of the study includes conferences of young scholars – bachelors, undergraduates, and graduate students – held by the University of Tyumen, Perm State University and Perm State Humanitarian Pedagogical University, Udmurt State University, South Ural State University and South Ural State Humanitarian Pedagogical University, Ural State Pedagogical University and Ural Federal University. Collections of scholarly articles by young researchers, both autonomous and formed on the basis of the results of conferences, also fall within the field of view of the authors. As a result of the analysis performed, a conclusion is made about the diversity and high degree of intensity of youth science in the Urals. The article notes the diversity and the creative component in the organization of scholarly events such as conference-assembly, art festival, section of a collection of scholarly papers which also presents the research activity of its young participants, etc. The article emphasizes such features typical of practically all conferences/collections of papers as drawing on the traditions of the older generations of the scholars preserving the continuity in the development of the scientific schools of literary studies and interdisciplinarity of research strategies associated either with the involvement of the methodological principles of adjacent humanities or translation of the text into a different semiotic code (cinema, theatre). The study stresses the urgency of addressing the research topics that are associated with the study of the current literary situation and are aimed at considering the problems of poetics, genreology, receptive aesthetics, and interpretation and author’s strategies through the prism of semiotic and intertextual approaches. Equally popular are the works that reveal the connections of the artistic world of a work with the space of auto-documentary literature, show the gender identity of the text in classical and modern literature, and study the psychological aspects of perception of literary texts for children and adults.